The Importance of Consuming Vegetables For Body Health - Solin, Aribah; Bara, Haniva Batu; Auzi, Mawar Islami; Tanjung, Cindy Agustiana; Amirul, Bani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The human body needs a balanced diet to maintain overall health and well-being. Among the important food groups, vegetables play a key role in providing essential nutrients, vitamins and minerals that promote health. The purpose of this study is to investigate the importance of vegetable consumption on body health. A comprehensive review of the available literature found that eating vegetables has many benefits for the body, including reducing the risk of chronic diseases, improving digestion and strengthening the immune system. The results of this study highlight the importance of adding vegetables to the diet to maintain optimal health.